2002
DOI: 10.1046/j.1563-2563.2002.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Surgical Therapy of Hepatic Colorectal Metastasis

Abstract: Summary: Background: Liver resection represents the only cure for patients with hepatic metastases from colorectal cancers.
Methods: The discussion will address which patients should be considered for hepatic resection, what are the appropriate diagnostic modalities to employ, and what are the hallmarks of surgical therapy. The biologic determinants of recurrence as the basis for rational patient selection for hepatectomy will be addressed. This review will then concentrate on recent data guiding adjuvant ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that an untreated disease is rapidly fatal, with a median survival period of 5–10 months. Patients with limited liver metastases, when left untreated, had 1-, 3-, and 5-year survival rates of 77%, 14%–23%, and 2%–8%, respectively [18][19]. Such patients are now considered candidates for resection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an untreated disease is rapidly fatal, with a median survival period of 5–10 months. Patients with limited liver metastases, when left untreated, had 1-, 3-, and 5-year survival rates of 77%, 14%–23%, and 2%–8%, respectively [18][19]. Such patients are now considered candidates for resection.…”
Section: Discussionmentioning
confidence: 99%